Pertumbuhan Ikan Mas Koki pada Sistem Vertiqua (Vertical Aquaculture) - Nadyra Esa Oktaviani; Robin Robin; Neneng Nurbaeti (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This research was carried out for approximately 1 month from 17 January – 05 March 2022. In situ measurements included temperature (Suhu), acidity (pH), and dissolve oxygen (DO). Directly in the Lab. Aquaculture Biotechnology Fakulty of Agriculture University of Muhammadiyah Sukabumi. the test included testing the ex situ water quality at the IPB University Laboratory. Testing ammonia and alkalinity. The results of the above objectives show a comparison of the growth of water quality in the vertiqua system (Vertical Aquaculture), to determine the effectiveness of the vertiqua system in goldfish cultivation on growth, feeding effeciency, and water quality.